DINAMIKA PENYELENGGARAAN MADIN TAKMILIYAH DI KABUPATEN JEPARA - Ali As'ad; Muhammad Natsir; Ahmad Ali Munir (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
Madrasah Diniyah as a non-formal educational institution based on religion in Indonesia whose existence has been acknowledged in the Uandang Law according to Director General number 3201 education letter 2013 The existence and role of the Takmiliyah Diniyah Education Institute in this country has no doubt. This existence is strengthened by the establishment of Law Number 20 of 2003 concerning with the National Education System in which there is an effort to accommodate the existence of this institution to be part of the education system in this country, when the Diniyah Madrasah Takmiliyah is part of non-formal education. This research focuses on answering two formulated problems: (1) how the implementation of MADIN in Jepara Regency is; (2) what factors have caused the Madrasah Diniyyah Takmiliah at Jepara unable to compete other educational institutions.; (3) What problems are faced by MADIN and how do the solutions work. The design of this study is a case study (field study) or field research. This study aims to examine in depth the causal factors that the education of the Dinniyah Takmiliyah madrasa is considered to be less competitive in education world.